2009
DOI: 10.1673/031.009.4901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Darker, Intermediate and Lighter Phenotypes of Body Melanization on Desiccation Resistance inDrosophila melanogaster

Abstract: A possible link between melanization and desiccation resistance can be inferred if within population differences in melanization find significant correlations with desiccation resistance and its mechanistic basis i.e. rate of water loss/hr. Accordingly, darker, intermediate and lighter phenotypes of body melanization were analyzed in wild and laboratory reared Drosophila melanogaster L. (Diptera: Clyclorrapha) populations from highland and lowland sites located in close proximity at five different latitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
1
30
0
4
Order By: Relevance
“…Under this resistance hypothesis, melanic individuals have a selective advantage in more desiccating environments, like montane environments, than less or non-melanic individuals. Melanic Drosophila morphs were found in more-desiccating environments (higher altitudes) than non-melanic morphs (Parkash et al, 2008b(Parkash et al, , 2009, whereas darker abdominal pigmentation positively correlated strongly with altitude in sub-Saharan D. melanogaster populations (Pool and Aquadro, 2007). However, the altitudinal distribution of melanic H. maori differs from this pattern.…”
Section: Discussionmentioning
confidence: 81%
“…Under this resistance hypothesis, melanic individuals have a selective advantage in more desiccating environments, like montane environments, than less or non-melanic individuals. Melanic Drosophila morphs were found in more-desiccating environments (higher altitudes) than non-melanic morphs (Parkash et al, 2008b(Parkash et al, , 2009, whereas darker abdominal pigmentation positively correlated strongly with altitude in sub-Saharan D. melanogaster populations (Pool and Aquadro, 2007). However, the altitudinal distribution of melanic H. maori differs from this pattern.…”
Section: Discussionmentioning
confidence: 81%
“…Regarding other environmental factors, a strong association of pigmentation intensity and desiccation resistance has been reported within and among D. melanogaster populations from India (Parkash et al, 2008a(Parkash et al, , 2008b(Parkash et al, , 2009, which suggests that humidity related adaptation may be important in some regions. However, a study on longitudinal cline of pigmentation variation in a different species, D. americana, did not find any association between pigmentation and desiccation resistance (Wittkopp et al, 2011;Clusella-Trullas and Terblanche, 2011).…”
Section: Pigmentation Variation In Drosophilamentioning
confidence: 99%
“…The first report of the trident polymorphism from a natural population was by the pioneers of Drosophila geneticists, Morgan and Bridges (1919), followed by Jacobs (1960Jacobs ( , 1961, and David et al (1985). What is particularly noticeable about the studies on pigmentation variation within this species is that a clinal variation in pigmentation intensity is repeatedly observed along altitude or latitude or both (David et al, 1985;Munjal et al, 1997;Pool and Aquadro, 2007;Parkash et al, 2008aParkash et al, , 2008bParkash et al, , 2009Telonis-Scott et al, 2011). These observations of non-random distribution of the phenotype can be a circumstantial evidence that supports environmental adaptation playing a role in shaping the diverse patterns of body pigmentation.…”
Section: Pigmentation Variation In Drosophilamentioning
confidence: 99%
“…The majority of insect water loss is across the cuticle, due to the high surface area to volume ratio (Gibbs, 2002;Hadley, 1994), and reduced rates of cuticular water loss (CWL) are associated with greater resistance to desiccation (Parkash et al, 2008). Cuticular permeability can be modified via structural changes to the cuticle, such as melanisation (Hadley, 1978;Parkash et al, 2009aParkash et al, , 2009b, or through changes to the quantity and identity of cuticular hydrocarbons (CHCs) (Gibbs and Pomonis, 1995). It has been suggested that cuticular permeability can be reduced by increasing total amount, saturation, and chain length of CHCs (Gibbs and Pomonis, 1995).…”
Section: Introductionmentioning
confidence: 99%